Energy Sector Experience of Output-Based Aid - Global Partnership on Output-Based Aid (World Bank, Washington, DC, 2016)
Sustainable development goals (SDGs) placed access to basic services at the center of international development in 2016-2030. Out of 17 goals, five address the access of poor people to basic services: to health in SDG3, to education in SDG4, and SDG5, to water and sanitation in SDG6, to energy in SDG7, and to urban services in SDG11. The mutually reinforcing relationship between electricity access, economic development, and poverty reduction is well established. The SDGs framed access to basic services as a matter of dignity. The SDG synthesis report promotes self-reliance of developing countries rather than just the North-to-South aid, as the challenge of poverty and exclusion extends beyond charity to the hungry and the most deprived. Directly or otherwise, access to electricity results in progress in all dimensions of human welfare and development including education, health care, access to water, essential communications and information as well as simple financial transactional services, income generation, and environmental sustainability. Also, a positive relationship can be seen between electricity access and the human development index (HDI).